The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/qai.0b013e3181b323ff
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Mother-to-Child Transmission of HIV-1 Through Breastfeeding by Treating Mothers With Triple Antiretroviral Therapy in Dar es Salaam, Tanzania: The Mitra Plus Study

Abstract: HAART given to HIV-infected mothers in late pregnancy and during breastfeeding resulted in a low postnatal HIV transmission similar to that previously demonstrated in the Mitra study in Dar es Salaam using infant prophylaxis with 3TC during breastfeeding. The extended maternal prophylaxis with HAART for prevention of mother-to-child transmission of HIV-1 for breastfeeding mothers who do not need HAART for their own health should be further evaluated and compared with the use of infant postnatal antiretroviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(165 citation statements)
references
References 31 publications
9
144
1
8
Order By: Relevance
“…Two studies with CD4 cut-offs of 500 29 Fourteen studies were reviewed, including a total of 2 663 participants (Table 2). 4,5,[27][28][29][30][31][32][33][34][35][36][37][38] One study was funded by the NVP manufacturer Boehringer Ingelheim. 30 The studies, mostly undertaken between 2001 and 2006, were predominantly observational with participant numbers ranging from 17 to 703.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies with CD4 cut-offs of 500 29 Fourteen studies were reviewed, including a total of 2 663 participants (Table 2). 4,5,[27][28][29][30][31][32][33][34][35][36][37][38] One study was funded by the NVP manufacturer Boehringer Ingelheim. 30 The studies, mostly undertaken between 2001 and 2006, were predominantly observational with participant numbers ranging from 17 to 703.…”
Section: Resultsmentioning
confidence: 99%
“…The CD4 cut-off was 250 cells/µl for toxicity analyses in all studies, except for one (CD4 cut-off of 200 cells/ µl). 35 Mean time to toxicity ranged from 27 to 74 days. The overall frequency of NVP toxicity was 8.3%, driven mostly by hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, cohort [293][294][295][296] and RCT [66,78,297] data from Africa have shown that ART can significantly reduce the risk of HIV transmission from breastfeeding. This is in settings where breastfeeding is not affordable, feasible, acceptable, sustainable and safe, and mortality from formula feeding outweighs additional mortality from HIV transmission by breastfeeding [298,299].…”
Section: Infants Born To Hiv-positive Mothers Should Follow the Routimentioning
confidence: 99%
“…I en åpen kohortstudie med brysternaerte barn fra Tanzania ga lamivudin som perieksposisjonsprofylakse til barnet en smitterisiko ned mot 1 % ved seks måneders alder (19). I en helt fersk oppfølgingsstudie fra samme studiegruppe var det tilsvarende gode resultater ved bruk av HAART-behandling hos mor (20).…”
Section: Internasjonal Medisinunclassified